Personal Recovery and Its Determinants Among People Living With Schizophrenia in China - Yu, Yu; Xiao, Xi; Yang, Min; Ge, Xiao-ping; Li, Tong-xin; Cao, Gui; Liao, Ying-jun (Frontiers in Psychiatry, 2020)
Objective: The past few decades have seen an evolution in the understanding of recovery from a clinical-based view that focuses on symptoms and functioning to a more consumer-oriented perspective that focuses on personal recovery. The present study aimed to assess personal recovery among people living with schizophrenia and determine its predictors. Methods: This cross-sectional study recruited a random sample of 400 people living with schizophrenia (PLS) from twelve community health centers of Hunan, China. Recovery was assessed using the short-form 8-item Recovery Assessment Scale (RAS-8). PLS disability and functioning were assessed using the 12-item World Health Organization Disability Assessment Schedule 2.0 (WHODAS 2.0) and the Global Assessment of Functioning (GAF), respectively. Results: Participants had a mean personal recovery score of 20.29 (SD: 9.31, Range: 8–40). Personal recovery was predicted by both socio-demographic and clinical characteristics. Older age (r = −0.17, p < 0.001), being female (r = −2.29, p = 0.019), and higher disability (r = −0.22, p < 0.001) were independently associated with worse personal recovery, while having a college education (r = 5.49, p = 0.002), and higher functioning (r = 0.09, p = 0.017) were independently associated with better personal recovery. Conclusion: Interventions to improve recovery among PLS may be best served by reducing the impact of disability and improving functioning, with targeted interventions for individuals who are older, female and less educated in order to increase their likelihood of recovery.